"Ch’assai t’intendo"; the narrative of seduction and the seduction of narrative in an early fourteenth-century fresco - Simmons, Laurence (Spunti e Ricerche, 2016)
Narrative studies have primarily dealt with texts of a written fictional genre and this in turn has served to marginalise the performative and contractual problems of narrative whereby each story results from and has the power to change the relationship between narrator and narratee. This present reading aims to redress some of this imbalance by examining an early fourteenth-century fresco cycle on a secular theme as an instance of narrative.